Management of in-flight medical emergencies : a study on knowledge and confidence among Emergency Department doctors in Hospital Universiti Sains Malaysia - Wee, Chong Woon (2020)
Introduction In-flight medical emergencies are common and the numbers are expected to rise as the world population ageing. This research is to study on knowledge and confidence among emergency department doctors in the management of in-flight medical emergencies. Method This cross-sectional study used a self-administered questionnaire conducted among doctors in the emergency department of a tertiary hospital in the east-coast of Malaysia from January 2019 to January 2020.The validated questionnaire which was adapted from a study done in the United States (Katzer et al) consists of a total 3 sections on demographic data, confidence and knowledge on the management of inflight medical emergencies. Result There were a total of 132 respondents. Majority of respondents were medical officers (53.8%) and most of them were divided in the age group 25-30 years (43.2%) and 31-35 years (46.2%). In addition, majority of respondents had working experience of 5 years and less in clinical field (47.7%). The mean knowledge score was 5.22/9. Only 38.6% of doctors felt confident in managing in-flight medical emergencies. There was a significant association between number of years working in clinical field with knowledge level (P=0.032) and confidence level (P=0.006). However, there was no significant association between knowledge and confidence level with previous healthcare training. Conclusion Our current local training should include management of in-flight medical emergencies to improve the knowledge and confidence level among doctors.